2008
DOI: 10.3200/gntp.169.3.245-260
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems of Parents of Typically Developing Children and Parents of Children With Autism

Abstract: Few researchers have investigated the relation of children's sleep problems to their parents' sleep problems. Children with autism have been reported to evidence greater sleep problems than do typically developing children (C. D. Hoffman, D. P. Sweeney, J. E. Gilliam, & M. C. Lopez-Wagner, 2006; P. G. William, L. L. Sears, & A. Allard, 2004). In the present study, parents (N = 106) of children independently diagnosed with autism (4-16 years of age; M= 8.20 years, SD = 2.69 years) reported greater sleep problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 53 publications
7
44
1
1
Order By: Relevance
“…Using objective sleep measurements, our study adds to the growing body of evidence showing an association between sleep initiation and sleep maintenance insomnia and daytime behavior in children [10,13]. Further, our findings augment previous reports showing associations between sleep in the child and parent [7,24,25] and extends previous reports by showing that disrupted nighttime sleep in the child may be associated with daytime sleepiness in the mother. Of interest, our study is one of the first that we are aware of that has reported the impact of a child’s early morning awakening on daytime behavior in children with autism, as well as children with typical development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Using objective sleep measurements, our study adds to the growing body of evidence showing an association between sleep initiation and sleep maintenance insomnia and daytime behavior in children [10,13]. Further, our findings augment previous reports showing associations between sleep in the child and parent [7,24,25] and extends previous reports by showing that disrupted nighttime sleep in the child may be associated with daytime sleepiness in the mother. Of interest, our study is one of the first that we are aware of that has reported the impact of a child’s early morning awakening on daytime behavior in children with autism, as well as children with typical development.…”
Section: Discussionsupporting
confidence: 82%
“…We found few differences between the mothers of the autism spectrum disorder–good sleepers, autism spectrum disorder–poor sleepers, and typical development across the majority of sleep parameters. Whereas parents of children with autism spectrum disorder were previously reported to have shorter actual sleep time then parents of children with typical development [7] in our study differences were found only with sleep onset insomnia and the number of wake-bouts during the night. Previous studies, using parental self-report have differed in their findings looking at maternal sleep across varying types of sleepers.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Sleep disturbances are the most frequent comorbid conditions for children with ASD [2]. Sleep disturbances are linked to a wide range of negative outcomes, including worsened autistic symptoms, impairments in cognitive and daily functioning in children with ASD [3][4][5][6], and elevated mental problems in their parents [7][8][9]. Furthermore, both cross-sectional [10] and longitudinal [11] evidence suggest that sleep disturbances in children with ASD can persist throughout childhood into later life.…”
Section: Introductionmentioning
confidence: 96%
“…Parents also typically report that their children have sleep problems more frequently, including significant sleep onset and maintenance problems (Malow and McGrew 2008), irregular sleep-wake patterns, early waking, and poor sleep routines (Patzold et al 1998;Mindell et al 2006;Quine 2001;Schreck and Mulick 2000;Honomichl et al 2002). Sleep problems have also been shown to be related to problems with daytime behavioral functioning in children with autism spectrum disorders (Malow et al 2006;Schreck et al 2004) and to sleep problems in the parents of children with autism (Lopez-Wagner et al 2008).…”
Section: Noncontingent Reinforcementmentioning
confidence: 99%